Portable Coolbox Design For Milk Storage - Hayati, Enty Nur; Radyanto, Moh. Riza; Ekoanindiyo, Firman Ardiansyah; Prihastono, Endro (Journal of Applied Engineering and Technological Science (JAETS), 2022)
The SN Multi-Business Cooperative (KSU) was founded in 2011 in Semarang Regency. This cooperative operates in the storage of pure cow’s milk with a total of around 300 milk farmers located around the cooperative. The problem that often arises is the dependency on receiving milk by the milk factory. Milk that has been sent to the dairy factory can be rejected by the milk factory for various reasons. In the field of marketing, KSU SN established a business entity with the name CV MSN which is located on Jalan Tirto Agung, Semarang. Product delivery logistics activities have so far been carried out with four-wheeled vehicles and using two-wheeled vehicles. To transport milk, each driver uses a bag or styrofoam which is used to transport milk products. Apart from being impractical, the transport process is messy, and the milk temperature cannot be maintained. To overcome this problem, milk transport boxes are designed to be able to transport milk more effectively, maintain product temperature, be ergonomic and increase the capacity of milk that can be distributed because previously they used boxes made of cork or styrofoam. This motorbike will be equipped with a milk storage device in the form of a detachable cooler box or a portable cool box. In this design the anthropometry or body dimensions used are the forward span with the 50th percentile so that all workers can use this tool. with the portable tolbox design, increasing the duration of milk storage time from 8 hours to 24 hours so that marketing and sales departments can take longer to distribute milk products and distribute more capacity